Assessment of the efficacy of topical antiandrogen; spironolactone in patients with androgenetic alopecia by dermoscopy - Mahdy Hussein, Sherief; M Soliman, Ahmed; Hosam Abd El-Alim, Sameh; Alaa Kassem, Ahmed; Emam, Hanaa; Shehata, Hany; Abdelmaksood Rabie, Ahmad; Farouk Aly, Hanan; Bakr El Zawahry, Yasmin (Journal of Pakistan Association of Dermatologists, 2022)
Background: Androgenetic Alopecia (AGA) is a non-scarring alopecia characterized by progressive miniaturization of hair follicles with a distinctive distribution in genetically prone males & females. Topical Spironolactone is commonly used as off-label anti-androgen for managment of AGA. Objective : Assessing role of topical 1% spironolactone on hair thickness & count in patients with AGA using dermoscopy. Methods: 26 patients (16 males and 10 females) with ages ranging from 26 to 59 years with a mean of 42.77 Â±6.62 SD. received topical 1% spironolactone solution to apply on the scalp once daily for at least six months. All patients had positive family history. Dermoscopy was performed on fixed areas on the scalp. Images were taken with a digital camera that was connected to the dermoscope just before starting treatment and after 6 months continuous treatment. Results: Significant increase in total terminal, terminal thick and total hair count in female patients along with a significant increase in total terminal, terminal thin, vellus and total hair count in male ones after treatment with topical 1% spironolactone were seen. However, thin and vellus hair in female and thick hair in male revealed no significant difference post spironolactone treatment.Conclusion: Spironolactone is an effective & harmless treatment in both females & males with AGA.